2000
DOI: 10.1093/ajcn/71.5.1085
|View full text |Cite
|
Sign up to set email alerts
|

Purified eicosapentaenoic and docosahexaenoic acids have differential effects on serum lipids and lipoproteins, LDL particle size, glucose, and insulin in mildly hyperlipidemic men

Abstract: Background: Regular consumption of nϪ3 fatty acids of marine origin can improve serum lipids and reduce cardiovascular risk. Objective: This study aimed to determine whether eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids have differential effects on serum lipids and lipoproteins, glucose, and insulin in humans. Design: In a double-blind, placebo-controlled trial of parallel design, 59 overweight, nonsmoking, mildly hyperlipidemic men were randomly assigned to receive 4 g purified EPA, DHA, or olive oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
361
10
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(409 citation statements)
references
References 53 publications
34
361
10
4
Order By: Relevance
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, long-chain nÀ3 polyunsaturated fatty acids have been found to be associated with enhanced glucose metabolism (Feskens et al, 1991;Adler et al, 1994;Feskens et al, 1995;Baur et al, 1998;Ekblond et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Thorsdottir et al, 2004) and to lower serum free fatty acid (FFA) concentrations (Gustafsson et al, 1998), although there are also contradictory results (Salomaa et al, 1990;Borkman et al, 1993;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Bjerregaard et al, 2000;Mori et al, 2000;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004). It is not known whether some of the discrepancies in previous results could be attributed to differences in the genetic background of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In overweight, treated hypertensive patients (52) and in dyslipidaemic men (53) , n-3 fatty acids increased HDL cholesterol due primarily to an increase in HDL 2 -cholesterol subfraction. A reduction in hepatic very-low density lipoprotein cholesterol synthesis probably contributes to the fall in plasma TAG.…”
Section: Effects On Plasma Lipids and Lipoproteinsmentioning
confidence: 98%
“…The erythrocyte fraction was washed and packed. Processed plasma and erythrocyte samples were stored at À80 1C until transferred to a separate laboratory for PUFA analysis by gas liquid chromatography using a Hewlett-Packard model 5980A gas chromatograph (Mori et al, 2000). Individual fatty acids were calculated as a relative percentage with the evaluated fatty acids set at 100%.…”
Section: Recruitmentmentioning
confidence: 99%